Social Considerations in Political Territorial Organization of Society - Adejuyigbe, Omolade (Obafemi Awolowo University Press, 2013)
In choosing the topic Social Consideration in Political Territorial Organization of Society, I intend to highlight the general principles derived from studies of the evolution, organisation and cohesion of political units and discuss their applicability to the solution of relevant problems in this country. To this end the rest of the lecture is divided into five parts, namely: basic units for political territorial organization; social considerations in the merger of the basic units; social considerations encouraging separation from established political units; social considerations in the delimitation of the boundaries of political units; and relevance to Nigeria.